Whole β-glucan particle attenuates AOM/DSS-induced colorectal tumorigenesis in mice via inhibition of intestinal inflammation - Xie, Yewen; Shao, Fang; Duan, Xuehan; Ding, Jun; Ning, Yongling; Sun, Xiao; Xia, Lei; Pan, Jie; Chen, Jie; He, Shuyan; Shen, Dong; Qi, Chunjian (Frontiers in Pharmacology, 2023)
Yeast β-glucan is a polysaccharide purified from the Saccharomyces cerevisiae cell wall, and its multiple biological activities are essential for immune regulation. However, the effect of β-glucan on the intestinal immune response during colitis-associated colorectal cancer (CAC) is unclear. Here, we explore the possible role of β-glucan in the development of CAC. Wild type (WT) mice with CAC induced by azoxmethane (AOM) and dextran sodium sulfate (DSS) had fewer tumors than untreated mice after oral β-glucan because of increased antitumor dendritic cells (DCs) in the tumor microenvironment, resulting in more CD8+ T cells and the production of related cytokines. β-glucan also increased resistance to DSS-induced chronic colitis by reshaping the inflammatory microenvironment. These data suggest that β-glucan improves experimental intestinal inflammation and delays the development of CAC. Therefore, β-glucan is feasible for treating chronic colitis and CAC in clinical practice.